(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study examines the effect of green intellectual capital on the sustainability performance of Indonesian companies. Green Intellectual Capital according to Chen (2008) is an intangible asset of a company, including knowledge, ability, experience and innovation in the field of environmental protection. According to Chen (2008), green intellectual capital has three components, namely green human capital, green structural capital, and green relationship capital. All three are important factors to bring the company to a competitive advantage.The research was conducted by accessing financial reports from the Indonesia stock exchange website (www.idx.co.id). In this study, the method for analysis was carried out in two ways, namely descriptive analysis and inferential analysis. Descriptive analysis describes each of the variables studied, while inferential analysis shows the relationship between each variable obtained through data processing. The method of estimating the results of the study uses a complete panel data regression analysis (balanced panel data) with the StataSE 14 device to answer the research questions.From the results of the study, it is known that green human capital has a significant positive effect on sustainability performance, while green structural capital has a significant positive effect on sustainability performance, and green relational capital has a significant positive effect on sustainability performance. Companies in Indonesia are more concerned about green intellectual capital. which consists of Green human capital, Green structural capital and Green relatinal capital as indicators of sustainability performance